Income inequality, productivity, and international trade - HSU, Wen-Tai (Institutional Knowledge at Singapore Management University, 2018)
This paper discusses the effect of income inequality on selection and aggregate productivity in a general equilibrium model with non-homothetic preferences. It shows the existence of a negative relationship between the number and quantity of products consumed by an income group and the earnings of other income groups. It also highlights the negative effect of a mean-preserving spread of income on aggregate productivity through the softening of firms’ selection. This effect is however mitigated in the presence of international trade. In a quantitative analysis, it is shown that an excessively large mean-preserving spread of income may harm the rich as it raises firms’ markups on their purchases. This is contrary to the general belief that income inequality benefits the rich.